Bridging the gap of graduates' English language communication skills towards employability / Haslena @ Lena Ismail - Ismail, Haslena @ Lena (2013)
The purpose of this study is to explore and highlight the critical thinking of employers on the desired quality of English Language communication skills expected of graduates. The study employs a qualitative research design with interviews with three key industry employers, and document analysis of a Bachelor of Education in TESL program of a public institution of higher learning (IHL). Findings from this study show that the industry needs graduates to master the English Language communication skills' attributes in speaking, writing, reading and listening. The use of simple, plain and comprehensive English Language, besides basic general knowledge, courtesies and deportment is much sought after by employers. During employment, retraining in English Language communication skills should be continued with high commitment of graduate employees to practice and promote English Language communication skills at workplace. A standard mechanism in assessing graduates' communication skills should be embedded in academic curriculum whilst students are still at IHL. It could be done by a collaboration of IHL and industry. The study also shows that TESL degree program embeds the communication skills required by employers; however it can be further improved with the inclusion of business inclined elective courses which could help to enhance the marketability and employability of TESL graduates beyond the teaching profession.